The militarization of the urban question - Souza, Marcelo Lopes de (Pontifícia Universidade Católica de São Paulo, 2012)
This article examines the significance of Police Pacification Units (UPPs) in the context of thecurrent urban geopolitics and the different aspects of the expression “re-conquest of territory”widely used by different agents of the State. It involves an explicit militarization of the urbanquestion. If earlier the urban question was reduced to a “case for the police,” now we aremoving towards turning it into a wholly institutionalized military question.